Upregulation of smooth muscle Rho-kinase protein expression in human asthma. Issue 3 (5th March 2020) - Wang, Lu; Chitano, Pasquale; Paré, Peter D.; Seow, Chun Y.
The lack of bronchodilatory response to deep inspiration in asthmatics is thought to be partially due to reduced airway distensibility [1, 2], possibly caused by an increase in airway smooth muscle (ASM) tone and stiffness [3]. Rho-kinase (ROCK) is known to play a role in regulating ASM tone [4] and ASM cytoskeletal stiffness [5]. An important phenotypic change is associated with human asthma: the protein expression of both isoforms of Rho-kinase, ROCK1 and ROCK2, is increased in the smooth muscles of intra-parenchymal airways and in the pulmonary blood vessels http://bit.ly/2pPfyxH